Tree species composition and environmental relationships in a Neotropical swamp forest in Southeastern Brazil - Teixeira, Aloysio de P. [UNESP]; Assis, Marco A. [UNESP]; Siqueira, Fernando R.; Casagrande, José C. (Springer Nature, 2008)
We examined the relationships between topography, soil properties and tree species composition in a Neotropical swamp forest in southeastern Brazil. Plots were sampled in the forest, encompassing three different soil ground water regimes along the topographical declivity. All non-climbing plant individuals with trunk height >1.3 m were sampled. A canonical correspondence analysis-CCA-of the species-environmental relationships grouped tree species according to drainage and chemical soil conditions. A total of 86 species were found, being 77 species in the inferior, 40 species in the intermediate and 35 species in the superior topographic section. Some species were among the 10 most abundant ones, both in the overall sampled area and in each topographical section, with alternation events occurring only with their abundance position. However, substantial differences in floristic composition between sections were detected in a fine spatial scale, due to higher number of species, diversity index (H′) and species unique (exclusives) in the inferior topographic section. These higher values can be attributed to its higher spatial heterogeneity that included better drained and seasonally waterlogged soils, higher soil fertility and lower acidity. The increase of the soil water saturation and the uniform conditions derived from the superficial water layer has led to a lower number of species and an increase on the palm trees abundance in the intermediate and superior sections. Our results showed that at a small spatial scale niche differentiation must be an important factor related to the increase of the local diversity. The wide distribution of the most abundant species in the studied area and the increase of local diversity corroborate the pattern of distribution of species in larger scales of swamp forests, in which the most abundant species repeat themselves in high densities in different remnants. However, the floristic composition of each remnant is strongly variable, contributing to the increase of regional diversity. © 2008 Springer Science+Business Media B.V.
Keywords: Diversity; Fine spatial scale; Riverine forests; Semi-deciduous forests; Topographic gradient; Topography; Tropical Swamp forests; Waterlogged soils; canonical analysis; community composition; deciduous forest; groundwater; Neotropical region; soil chemistry; soil property; spatial variation; species diversity; species-area relationship; swamp forest; tropical forest; Brazil; South America